Analisis Keterampilan Metakognitif Calon Guru Biologi pada Perkuliahan Mikrobiologi - Nining Purwati (Postgraduate, University of Mataram, 2022)
The 21st century skills that must be possessed by pre-service biology teachers is metacognitive skills. Metacognition refers to a person's abilities about his cognition and everything related. This descriptive study aims to describe the level of metacognitive skills of pre-service biology teachers. The data collection procedure was carried out by a metacognitive skill rubric that integrated with essay test. The subjects of this study were 70 of pre-service biology teacher at Universitas Islam Negeri Mataram in the 2021/2022 academic year. The research data were analyzed descriptively by determining the percentage of metacognitive skill levels. The results showed that the mean level of pre-service biology teachersâ€™ metacognitive skills was â€œstarting to developâ€ (44.35). The pre-service teachers with â€œhave so developed categoryâ€ occupies the highest percentage (41%), while the lowest percentage is occupied by the category of â€œstill very riskyâ€ and â€œvery well developedâ€ with a percentage 6% of each